PREFERENSI KONSUMEN TERHADAP “PRIVATE LABEL” RITEL MODERN DIKAITKAN DENGAN KARAKTERISTIK KONSUMEN: STUDI KASUS PADA PRODUK GULA DI LOTTE MART BANDUNG - Elly Rasmikayati; Siti Tari Syamsiah; Agriani Hermita Sadeli; Bobby Rachmat Saefudin (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
PT Lotte Mart Shopping Indonesia Bandung, as one of the modern retailers in Bandung, has a number of products with private label, including sugar products. This study aims to analyze the relationship between consumer characteristics and consumer preferences for "private label" of sugar products at modern retailers Lotte Mart Shopping Indonesia Bandung. There were 42 research respondents who were private label consumers of sugar products at Lotte Mart who were determined using systematic random sampling technique. The data analysis tool used is cross tabulation. The results of the consumer preference research show that the most ideal size attribute according to the respondents is a sugar size of 1 kg, the private label sugar packaging design has been said to be attractive for the Choice L brand, the clarity of the information is still unclear because the information about the product is not shown clearly. so you have to really pay attention to the packaging of these products. The price attribute and the ease of obtaining sugar products are the main factors for consumers buying sugar products with this private label. Consumers who have a good preference for private label sugar are generally female, aged 36-50 years, have high school education, work as housewives with an income of Rp. 2,000,000-Rp. 4,000,000 per month.